Smart hybrid AC/DC distribution network - part II - Ng, Benedict Keng Chuan (Nanyang Technological University, 2022)
In-order to modernize our current traditional grid to a smart hybrid AC/DC bus system, this paper identifies three existing aspects of our AC grid system. Firstly, this study aims to identify the driving factors for peak demand with respect to the different consumer groups: “residential”, “commercial”, and “industrial consumer”. Next, using the publicly available data for Singapore to forecast maximum demand. Secondly, identify and explain the power quality problems that is caused by AC/DC loads onto the supply side grid system. A MATLAB simulation would be done for each of the power quality issue mention Thirdly, identify any technology that is currently available or being adapted for load management and control. A review behind the working principles and the components that make up the underlying technology will also be included